Pattern of skin disorder among patients attending skin outpatient department in tertiary care teaching hospital of district Almora: a retrospective study - Vikram S. Dhapola; Shashank Tyagi; Akbar A. Ahmed; Preeti Kumari (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Objectives: The aim of this study was to assess the morbidity profile of patients attending dermatology outpatient department in a tertiary care center of Kumaun region, North India. Methods: The present study was a retrospective, record-based cross-sectional study in which OP registers of the Department of Dermatology from July 2023 to July 2024 were analyzed. Skin diseases were grouped into different groups and the frequency of cases in each group was studied. Data analysis was performed using Microsoft Excel and Statistical Package for the Social Sciences software version 16. Results: A total of 5118 patients were recorded in this study. About 44.7% were male while 55.2 % were females. All disorders were broadly classified into non-infectious and infectious dermatoses, out of them acne was most common in non-infectious group while tinea was most common in infectious group. Conclusion: Infections and eczemas which could be managed in primary healthcare set-up contributed to the majority of the OP attendance of our tertiary care center. The peripheral institutions should be strengthened in manpower and the level of knowledge and skills.